Respuesta :

Answer: Choice C) [tex]\frac{8}{9}n - 1\frac{1}{3}[/tex]

====================================================

Explanation:

We multiply the outer term 4/9 with each term inside

  • (4/9) times (2n) = (4*2n)/9 = (8n)/9 = (8/9)n
  • (4/9) times (-3) = (4*(-3))/9 = -12/9 = -4/3

The improper fraction 4/3 converts to the mixed number 1 & 1/3

4/3 = (3+1)/3 = 3/3 + 1/3 = 1 + 1/3 = 1 & 1/3

So overall, we can say [tex]\frac{4}{9}(2n-3) = \frac{8}{9}n - 1\frac{1}{3}[/tex]

This is equivalent to saying [tex]\frac{4}{9}(2n-3) = \frac{8}{9}n - \frac{4}{3}[/tex]